1991
DOI: 10.1111/j.1471-4159.1991.tb02057.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Accumulation of the 1‐methyl‐4‐Phenylpyridinium Species into Mouse Brain Synaptosomes

Abstract: The mechanism of accumulation of 1-methyl-4-phenylpyridinium ion (MPP+), the toxic metabolite of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine, into neuronal terminals was studied using mouse brain synaptosomes as an in vitro model. Addition of MPP+ to synaptosomal preparations, essentially devoid of contamination by extrasynaptosomal mitochondria, resulted in its time- and concentration-dependent accumulation. Intrasynaptosomal concentrations of 79 and 106 microM were reached 10 and 30 min, respectively, after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Administration of MPTP alone may cause ATP depletion only in neuronal cells able to accumulate relatively high levels of MPP+ via the dopaminergic uptake system (Javitch et al, 1985). In contrast, after 2-DG treatment, the threshold of concentration for MPP' action may be lowered, and inhibition of mitochondrial respiration may become evident in the form of ATP depletion even in cells that do not actively accumulate MPP+ (Scotcher et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Administration of MPTP alone may cause ATP depletion only in neuronal cells able to accumulate relatively high levels of MPP+ via the dopaminergic uptake system (Javitch et al, 1985). In contrast, after 2-DG treatment, the threshold of concentration for MPP' action may be lowered, and inhibition of mitochondrial respiration may become evident in the form of ATP depletion even in cells that do not actively accumulate MPP+ (Scotcher et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The redistribution of MPP+ between the intra-and extracellular compartments reached equilibrium after approximately 4 h, suggesting that MPP+ efflux from astro- cytes follows a concentration-dependent gradient. Since MPP+ is a charged compound, this efflux is likely to be more adequately described as the result of a nernstian electrochemical gradient (Sayre, 1989;Scotcher et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has revealed that MPP+ possesses a low, but definite degree of lipid solubility since its positive charge is delocalized throughout the pyridinium ring (Reinhard et al, 1990). This property could provide a basis for the carrier-independent entry of MPP+ into cells and subcellular organelles (Reinhard et al, 1990;Scotcher et al, 1991). However, to date there has been no experimental evidence to support the possibility that MPP+ may be able to cross membranes in the opposite direction from the intracellular to the extracellular compartment.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned in the introductory section, the reported preferential toxicity of MPP + on dopaminergic neurons has been ascribed to its specific uptake by the dopamine carrier. However, it was recently reported that MPP + can be internalized by synaptosomes through a passive diffusion mechanism (Scotcher et al ., 1991) . It is possible, therefore, that the ion penetrates into the GABAergic neurons of the SNR by such a mechanism, causing disruption ofmitochondrial oxidative metabolism .…”
Section: Histologymentioning
confidence: 99%